Factors affecting survival and locoregional control in head and neck cSCCA with nodal metastasis. (20th December 2017) - Creighton, Francis; Lin, Alice; Leavitt, Erica; Lin, Derrick; Deschler, Dan; Emerick, Kevin
Abstract : Objectives: To determine factors affecting locoregional control (LRC) and disease‐specific survival (DSS) in patients presenting with regionally metastatic cutaneous squamous cell carcinoma (cSCCA) of the head and neck. Study Design: Retrospective review. Methods: Upon review of institutional pathology database to identify patients with metastatic cSCCA, 62 subjects met the inclusion criteria between 2009 to 2012. Cox proportional hazard ratios for DSS and LRC were calculated for tumor, patient, lymph node, and treatment variables. These factors included primary site, primary tumor grade, primary tumor perineural invasion, extent of primary tumor invasion, age, immune status, parotid nodal status, invasion of facial nerve by parotid tumor, cervical nodal status, extracapsular spread, number of nodes involved, adjuvant radiation therapy, and chemotherapy. All variables were analyzed to determine impact on LRC and DSS. A disease‐specific Kaplan‐Meier curve was determined for the entire cohort. Results: Five‐year survival was 56% for all patients. The presence of extracapsular spread (ECS) and bone involvement of the primary tumor site resulted in statistically significant decreases in DSS (hazard ratio (HR) 41.3 and 270, respectively; P = 0.02 and P = 0.008, respectively) and LRC (HR 8.41 and 11.1, respectively; P = 0.005 and P = 0.04, respectively). The remaining factors had no statistically significant effect on DSS or LRC. Conclusion: The presence of ECS in the metastatic lymph node and of bone invasion by the primary tumor appear to be important to the outcome of patients with metastatic cSCCA. These factors should be considered when developing multidisciplinary care plans and future investigations. Level of Evidence: 4. Laryngoscope, 1881–1886, 2018